Biometric assessments of the posterior fossa by fetal MRI: A systematic review. (18th December 2020) - Mckinnon, Katie; Kendall, Giles S.; Tann, Cally J.; Dyet, Leigh; Sokolska, Magdalena; Baruteau, Kelly Pegoretti; Marlow, Neil; Robertson, Nicola J.; Peebles, Donald; Srinivasan, Latha
Abstract: Background: Posterior fossa abnormalities (PFAs) are commonly identified within routine screening and are a frequent indication for fetal magnetic resonance imaging (MRI). Although biometric measurements of the posterior fossa (PF) are established on fetal ultrasound and MRI, qualitative visual assessments are predominantly used to differentiate PFAs. Objectives: This systematic review aimed to assess 2‐dimensional (2D) biometric measurements currently in use for assessing the PF on fetal MRI to delineate different PFAs. Methods: The protocol was registered (PROSPERO ID CRD42019142162). Eligible studies included T2‐weighted MRI PF measurements in fetuses with and without PFAs, including measurements of the PF, or other brain areas relevant to PFAs. Results: 59 studies were included – 6859 fetuses had 62 2D PF and related measurements. These included linear, area and angular measurements, representing measures of PF size, cerebellum/vermis, brainstem, and supratentorial measurements. 11 measurements were used in 10 or more studies and at least 1200 fetuses. These dimensions were used to characterise normal for gestational age, diagnose a range of pathologies, and predict outcome. Conclusion: A selection of validated 2D biometric measurements of the PF on fetal MRI may be useful for identification of PFA in different clinical settings. Consistent use of these measures, both clinically and for research, is recommended.